Quality Management Practices and Quality Performance: A Thematic Analysis of Indonesia’s Health Service Provider - Amanda Acintya (The Indonesian Journal of Accounting Research, 2019)
Preceeding literature indicates that service organizations are lagging behind their manufacturing firms in terms of the effective deployment of Total Quality Management (TQM) practices aimed to achieve operational and strategic goals. Given the paucity of TQM researches in service and Non-for-Profit organization, the objective of this study is for our research object to shed some light on the current TQM practices of and their relation to the company’s quality performance. service organizations. A thematic analysis is used to develop the constructs of QM practices. TQM is divided into two themes which are Infrastructure or “Soft” Quality Management (QM) Practices and Core or “Hard” QM Practices. The former one stresses on the human aspects whereas the latter is on the methods and business techniques. Each theme will be further broken down into its subthemes which have correlation with quality performance based on past researches. The paper derives its primary insights from in-depth interviews with the employees of a university’s health service provider in Indonesia. It analyses inductively the employee’s perspectives of QM practices implemented in the organization.  This qualitative research confirms causal models suggested by past quantitative studies and depict the organization’s enthusiasm in implementing TQM practices and how those improve organization’s quality performance. This study illustrates considerably small theoretical-practical gap of QM practices that is on the supplier relationship. More importantly, this study underscores the differences in TQM implementation practices due to some industry‐specific factor.